Safety Study of Steel Structure of Weighbridge I Girder Against Hauling Trailer - Zulfikar, Ryan; Noor, Rusandi (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
Weighbridges play a vital role in coal mining operations. This study aims to calculate the stress range and fatigue life of steel bridge girder cross-sections. Using the numerical simulation method with the CSI Bridge v22 application, the maximum axial force of 197 kN and the minimum axial force of -74 kN were obtained. The axial force is determined from the first 3 spans of the bridge with a span length of 4 m. The span length of the weighbridge is 80 m. From the calculation, the maximum stress of 40.11 MPa and the minimum stress of -15.06 MPa were obtained, resulting in a stress range of 55.16 MPa. The nominal bending moment strength of the beam was found to be 0.56. This modeling allows the simulation of dynamic loads from a 400-tonne SDT truck (semi-trailer door tipper) passing over the bridge so that accurate stress range data can be obtained. Fatigue analysis was carried out using the Basquin equation using the constant C = 1x1012 and exponent m = 3, receiving a fatigue life of 0.006 (6.01x106) cycles assuming 30-40 hauling trucks passing over the weighbridge. The results of calculations and simulations obtained longitudinal and transverse profile dimensions of IWF 1000x520x18x31.